Potential Carbon Storage And Absorption In Forest Stands In The Campus Area Of Nusa Cendana University, Kupang City, East Nusa Tenggara - Naylom, Laucia Lelita Erci; Marimpan, Lusia Sulo; Sinaga, Pamona Silvia (Universitas Andi Djemma Palopo, 2025)
High campus activities such as studying, teaching, and offices as well as vehicle activities can produce very complex carbon emissions, the lack of green open space and vegetation in it can result in increased temperatures, and air pollution because the carbon produced by campus activities cannot be absorbed by vegetation. Green open space (RTH) aims to help absorb carbon dioxide in the air, improve atmospheric quality, lower temperatures and reduce air pollution levels. This research aims to determine the value of carbon savings and absorption as well as the economic valuation of carbon on the Undana campus, so that it can be used as a reference in managing green open space in the campus environment to reduce global warming. This research was carried out using a non-destructive method using allometric equations with plot placement purposively based on the level of vegetation density. The results of this research show that the value of carbon storage in stands in the Nusa Cendana University area is 66.32 tons/ha and the value of CO uptake2 in the Nusa Cendana University area of 243.40 Tons/Ha and a carbon economic valuation of 39,876.61 USD or equivalent to IDR 615,418,524.